Relationship between Employee-Organization Congruence (perceived) and Organizational Commitment in the Sri Lanka Apparel Sector - Perera, G. D. N.; Khatibi, Ali; Nawaratne, N.N.J. (My University, 2012)
The objective of this research paper was to investigate the relationship between perceived Employee-Organization congruence (EOC) and Organizational Commitment (OC) in the Sri Lankan apparel sector. The present study, which was part of a comprehensive study Employee-Organization congruence (EOC) and attitudes, empirically evaluated seven perceived EOC related factors that could have effect on EOC namely supportiveness, innovation, aggressiveness, attention to detail, outcome orientation, emphasis on rewards, team orientation and three OC factors ,that is affective, normative and effective commitments. The study involved 175 machine operators who were selected from 05 large garment factories in Sri Lanka. The results indicated that all the EOC variables were positively and significantly correlated to OC. This study would be an effective contribution in the existing body of knowledge. Human Resource Managers and other recruiters may be helped to recognize the significance of perceived EOC and OC as well as their relationship with each other for ensuring selection of machine operators. Perceived congruence in the organization, will help creating and maintaining a conducive environment for improving organizational commitment of the machine operators which will ultimately result in enhanced efficacy and effectiveness of the organization
Keywords: Relationship between Employee-Organization Congruence (perceived) and Organizational Commitment in the Sri Lanka Apparel Sector